PENGARUH PENGEMBANGAN DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PERUSAHAAN DAERAH AIR MINUM KABUPATEN GORONTALO - Yakup . (Universitas Nusa Cendana, 2016)
This study aimed to analyze the influence of Development and Job Satisfaction on EmployeeProductivity. The samples in this study were 72 employees of Regional Water Company (PDAM)in Gorontalo district which is determined by saturation sampling techniques. The collection of databy distributing questionnaires using 5-point Likert scale for measuring three variables. The analysistechnique is Multiple Linear Regression Analysis. The results showed that partially, Developmentand Job Satisfaction have positive effect on PDAM Gorontalo’s Employee Productivity. Inaddition, 76,6 percent of the increasing variation of Employee's Productivity can be explained bythe Development and Job Satisfaction, while the remaining 23.4 percent is influenced by othervariables that are not included in this research model.Keywords : Development, Job Satisfaction, Employee Productivity.